Bridging Networks and Skills: The Moderating Role of Capital Access in Enhancing Post-Migrant SMEs Performance - Nilla Apsary; Lela Nurlaela Wati; Rita Yuni Mulyanti (Research Synergy Foundation, 2025)
This study analyses the role of community networks, specifically social capital, human capital investment (HCI), and capital access, in strengthening the impact of both forms of capital on the performance of micro, small, and medium enterprises (MSMEs) established by former Indonesian Migrant Workers (post-PMI). This study employs a quantitative methodology with a causal framework to achieve its objectives. The sample consisted of owners or managers of post-PMI MSMEs guided by the Indonesian Migrant Worker Protection Service Centre (BP3MI) across 23 provinces in Indonesia, totalling 200 MSMEs. The data were analysed using moderated regression analysis. The results demonstrate that community networks, HCI, and capital access have a positive influence on the performance of post-PMI MSMEs. Capital access has a positive moderating effect on the influence of community networks on the performance of MSMEs. Capital access has an adverse moderating effect on the influence of HCI on the performance of post-PMI MSMEs. The results of this study make a significant contribution to the development of social and human capital theories, particularly in the context of post-PMI MSMEs. The availability of financial capital is crucial for leveraging the opportunities that emerge from social networks. The finding that capital access negatively moderates the influence of HCI on MSME performance highlights the importance of limitations in applying skills and knowledge without sufficient financial resources to implement them. This study presents a novel examination of capital access as a moderating variable in the performance of MSMEs particularly among of post-migrant workers, a topic that has not been previously addressed by researchers.